Advances in optical-sensing strategies for the on-site detection of pesticides in agricultural foods. (January 2022) - Umapathi, Reddicherla; Park, Bumjun; Sonwal, Sonam; Rani, Gokana Mohana; Cho, Youngjin; Huh, Yun Suk
Abstract: Background: Synthetic chemical pesticides play a significant role in increasing the overall yield and productivity of agricultural foods by controlling and eradicating pests, insects, and numerous plant-related diseases. The over-spraying of pesticides onto crops has escalated pesticide contamination of food products and water bodies, as well as disturbing ecological and environmental systems. In this regard, developing simple, low-cost, and rapid-sensing strategies and portable devices for the precise, efficient, rapid, and on-site detection of pesticide residues in agricultural fields is indeed necessary and urgently required for the wellbeing and safety of mankind and other species. Scope and approach: In this review, we make a comprehensive study of the up-to-date state-of-the-art research progress on the on-site sensing strategies and portable devices for the detection of pesticide residues in agricultural foods using paper-, liquid-, and gel-based optical-sensing techniques. Moreover, we delineate the detailed on-site detection mechanism and sensing behavior of the aforementioned strategies and discuss the challenges and future perspectives associated with the development of optical techniques. Key findings and conclusions: Recent scientific and technological studies based on optical sens ing strategies such as fluorescence sensors, target-responsive hydrogels, chemiluminescence assay, tube enzyme-linked immunosorbent assay, enzymatic fiber-optic biosensor, phosphorescence, lateral flow immunoassay, double-signal fluorescence strategy, wearable glove-based sensors, and paper-based sensors have made novel advancements and brought scientific insight for the on-site detection of pesticide residues in agricultural foods. This review provides significant insights and future perspectives that might serve as the basis for the design and development of novel optical sensors with applicability in various fields. Graphical abstract: Image 1 Highlights: The first systematic review of the optical-sensing strategies for the on-site detection of pesticide residues in agricultural foods. Optical sensors are identified as significant and rapid analytical tools for the on-site detection of pesticides. User-friendly optical-based portable devices for on-site use with rapid detection strategies are explicitly summarized. Advancements, challenges, and future perspectives of the optical sensors for the on-site detection of pesticides are discussed.